INTER-RATER RELIABILITY OF THE MATHEMATICS TEST INSTRUMENT AT JUNIOR SCHOOL - Destiniar Destiniar (USN Kolaka, 2017)
The purpose of this research was to know whether or not there was difference of interrater reliability coefficient about mathematics test which evaluated by 18 raters and 12 raters and analyzed using Fleiss Kappa method. Rater in this study as many as 60 people consisting of 20 mathematics teachers of the Junior School (SMP ), 20 lecturers of Mathematics Education, and 20 lecturers of FMIPA mathematics. Instruments assessed in the form of mathematical test instrument for class IX with a simple multiple choices. The reserach method used in the form of experimental methods and data obtained were analyzed by using t-test. The result obtained there was difference of interrater reliability coefficient about mathematics test which assessed by 18 raters and 12 raters. The interateral reliability coefficient of the class IX mathematics test analyzed using the Fleiss Kappa method and rated by 18 raters was higher than that assessed by 12 raters.